Adaptation of Bacillus thuringiensis to Plant Colonization Affects Differentiation and Toxicity - Yicen Lin (American Society for Microbiology, 2021)
Biologicals-based plant protection relies on the use of safe microbial strains. During application of biologicals to the rhizosphere, microbes adapt to the niche, including genetic mutations shaping the physiology of the cells.